The L-Arginine-asymmetric dimethylarginine ratio is an independent predictor of mortality in dilated cardiomyopathy - Anderssohn, Maike; Zugck, Christian (Journal of cardiac failure, 2012)
BACKGROUND: Asymmetric dimethylarginine (ADMA) is associated with increased mortality in patients with chronic heart failure but it remains unclear if the etiology of heart failure influences the prognostic value of dimethylarginines. METHODS AND RESULTS: L-Arginine, ADMA, and symmetric dimethylarginine (SDMA) were measured by liquid chromatography-tandem mass spectrometry in 341 patients with chronic heart failure due to dilated cardiomyopathy (DCM; n = 226) or ischemic cardiomyopathy (ICM; n = 115). Median (interquartile range [IQR]) ADMA and SDMA plasma levels were higher, L-arginine and the L-arginine-ADMA ratio were lower in patients with severe forms of heart failure (New York Heart Association (NYHA) functional class III or IV) compared with milder forms (NYHA functional class I or II) (ADMA 0.57 (0.14) μmol/L vs 0.54 (0.12) μmol/L [P < .001]; SDMA 0.47 (0.27) μmol/L vs 0.37 (0.13) μmol/L [P < .001]; L-arginine 81.8 (39.1) μmol/L vs 92.6 (39.3) μmol/L [P < .01]), but no significant differences were observed between the different etiologies. The L-arginine-ADMA ratio was associated with outcome only in patients with DCM. In multivariate analysis, the mortality risk of DCM patients was significantly lower for those in the highest quartile compared with the lowest quartile during a median observation time of 3.3 years (hazard ratio 0.31, 95% CI 0.11-0.88; P = .028, adjusted for other risk factors). CONCLUSIONS: DCM patients with unfavourable L-arginine-ADMA ratio are at increased risk for death.